No, it is not a direct variation.
2x = 2x + 0 Hence the constant term is 0 (zero)
2x + x + 2x + x = 6x
3x + 2x - 8x + 2x = -x
2x squared plus 2x plus xy plus y or 2x(x+1) + y(x+1) or (x+1)(2x+y)
It is 2x+(-2x) = 0
The LCM is 2x + y
-2x + 6 + 22 = -2x + 28
6 + 2x + 5 = 11 + 2x
2x^2 + 13x + 15 factored means that the two numbers must multiply to the constant (15) and add to equal the coefficient on the X (13). So it becomes: (2x + 3) (x + 5). If expanded, 2x*5 = 10x and 3 * x = 3x which add to 13x. And 5 * 3 = 15
6x with 3 over the x, because that is how many x's there are.
-6 + 4x + (9-2x) = -6 + 4x + 9 - 2x = [ 3 + 2x ]
x equals 4
It can be simplified to: 2x+33
it equals 13X.
5x + x - 6x + 2x = 2x
4x plus 3 plus 2x is equivalent to expression 6x plus 3.